Functional derengament of muscle system - Wojtyczek, Łukasz (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: center; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Functional derengament of muscles is one of the most common patological process in locomotor system. It may be the first link in a patological chain or it may result from many other problems. Despite the cause, there are two symptoms that always exsist in functional derengament of muscles: hypertonicity and pain. The paper presents the most common functional derengament of muscles in particular parts of the body.